The Wright brothers - Helfand, Lewis (Campfire graphic novels. Biography., 2011)
In graphic novel format recounts the lives of Wilbur and Orville Wright, and describes how their interest in doing things for themselves and their persistence led them to build the first working airplane when better-educated and financed men had failed.